Implementasi Modeling Based Learning Terhadap Penguasaan Konsep IPA dan self efficacy pada siswa SMP Materi zat Dan Perubahannya - Ike Rusdiana (Fakultas Keguruan Dan Ilmu Pendidikan, 2025)
The impetus for this study was rooted in the imperative to implement 21st-century learning strategies, with the objective of addressing students' challenges in comprehending abstract concepts in the natural sciences and cultivating robust academic self-efficacy. The primary objective of this study is to provide an in-depth description of curriculum implementation through the Modeling-Based Learning (MBL) approach in enhancing mastery of science concepts, while also analysing the level of self-efficacy among junior high school (SMP) students, particularly regarding the topic of matter and its changes. The research method employed is descriptive qualitative, focusing on natural phenomena in the classroom. The present study was conducted at SMP Negeri 2 Wuluhan, with a sample of 54 seventh-grade students selected to participate in the study. The data collection instruments included student worksheets (LKPD), which were utilised to capture visual artefacts or sketches of students' mental models at each stage; observation sheets of learning activities; a self-efficacy questionnaire; and documentation of activities. The analysis was conducted interactively in accordance with the model proposed by Miles, Huberman, and Saldaña. This model encompasses the following stages: data reduction, presentation of data in narrative and diagrammatic forms, and drawing validated conclusions. The findings of the study demonstrate that implementing MBL has yielded substantial, gradual improvements in students' conceptual understanding. In Stage 1 (Problematizing), all 54 participants focused on macroscopic concepts (Concept G). However, in Stage 5 (Promoting), there was a sharp increase in understanding of microscopic aspects; 54 students successfully identified molecules (concept A), and 51 to 53 students were able to explain chemical and physical changes at the molecular level. Furthermore, the implementation of MBL had a favourable effect on students' self-efficacy. The results of the questionnaire indicated that 36 students were in the moderate category and 6 in the high category in the magnitude dimension; 49 students were in the moderate category and 5 in the high category in the strength dimension; and 44 students were in the moderate category and 10 in the high category in the generality dimension. In conclusion, the present study demonstrates the efficacy of MBL in enhancing the quality of science learning, with benefits observed in both cognitive and affective domains.
Validasi dan Finalisasi oleh Ratna 11 Juni 2026
Keywords: Mastery of Science Concepts; Matter and Its Changes; Modeling-Based Learning; Self-Efficacy